2012
DOI: 10.1093/abbs/gms058
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of V-Ets erythroblastosis virus E26 oncogene homolog 2 in regulation of transcription activity of <italic>MDR1</italic> gene

Abstract: Over-expression of MDR1 confers multidrug resistance (MDR) in cancers and remains a major cause for the failure of chemotherapy. In the present study, we found that V-Ets erythroblastosis virus E26 oncogene homolog 2 (ETS2) could activate MDR1 transcription and P-glycoprotein (P-gp) expression in SGC7901 cells. Knockdown of ETS2 attenuated MDR1 transcription and P-gp expression, and increased the sensitivity of MDR cancer cells to cytotoxic drugs that were transported by P-gp in SGC7901/VCR cells. ETS2 could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In paclitaxel-resistant prostate cancer PC3 cells, ETS1 silencing inhibited the activity of the ABCB1 promoter, which contains ETS binding sites, reduced ABCB1 protein, and reversed resistance to paclitaxel [ 260 ] , an antimicrotubule drug. ETS mediated regulation of ABCB1 was verified in a gastric cancer cell line exhibiting enhanced ABCB1 expression and vincristine resistance using ETS2 overexpression combined with ChIP assays [ 261 ] . At the level of FGF, immunohistochemical studies of bladder cancer tissue from patients showed correlation between basic FGF and ABCB1 signals [ 262 ] .…”
Section: Classical Developmental Signaling Pathways In Abcb1 Regulati...mentioning
confidence: 99%
“…In paclitaxel-resistant prostate cancer PC3 cells, ETS1 silencing inhibited the activity of the ABCB1 promoter, which contains ETS binding sites, reduced ABCB1 protein, and reversed resistance to paclitaxel [ 260 ] , an antimicrotubule drug. ETS mediated regulation of ABCB1 was verified in a gastric cancer cell line exhibiting enhanced ABCB1 expression and vincristine resistance using ETS2 overexpression combined with ChIP assays [ 261 ] . At the level of FGF, immunohistochemical studies of bladder cancer tissue from patients showed correlation between basic FGF and ABCB1 signals [ 262 ] .…”
Section: Classical Developmental Signaling Pathways In Abcb1 Regulati...mentioning
confidence: 99%